DIGITALISASI ARSIP ADMINISTRASI UJI SERTIFIKASIKOMPETENSI DI LEMBAGA SERTIFIKASI PROFESI UNIVERSITAS INDONESIA - Grataridarga, Niko; Noor, Muhammad Usman; Mardiati, Wiwiet (Jurnal Vokasi Indonesia, 2023)
This study discusses the digitizing process of certified competency test paperwork at the University of Indonesia Profession Certification Bodies ((Lembaga Sertifikasi Profesi) LSP UI). The process was conducted online using a web-based application system. The administrative digitization process produces born-digital recordss as evidence of the implementation of the test process. This study aims to see how the process of digitizing the administration of this competency test is carried out. The process of digitizing the competency test activities identified what digital records were created and how they affected archive management and business processes at LSP UI. This research method uses a qualitative approach with a narrative description of the data analysis. Data were collected through observations of LSP certification test activities, interviews of the personnel involved, analysis of LSP documents, and literature studies. The results that can be reviewed are the process of digitization competency certification activities at LSP UI carried outs by creating a web-based administration system. From this web system, participants register, administer exams, to announce test results by online system and also create several digital records, including personal records of participants, assessors files, registration files, test implementation files and exam results. The conclusion obtained is that the digitalization of competency certification tests is much needed, especially amid the Covid-19 pandemic. Digitization simplifies business processes and LSP supervision. The next issue is how each of these digitization system can be integrated with digital records management in LSP in particular and the organization in general. In addition, the issue of duplication, authenticity, filing and indexing of digital records is also a homework for organizations to do.